INTERJECTIONS AS IDIOLECT MARKERS: A CORPUS-BASED APPROACH - Sliepushova, Anhelina (Studia Philologica, 2021)
The article focuses on interjections that constitute idiolect of The Simpsons characters. For this purpose the subcorpora of Homer Simpson, Marge Simpson, Bart Simpson and Krusty the Clown have been analyzed by means of corpus and discourse analysis. A focus is made on wordlists and keyword lists that identify statistically the most frequent and salient words of the corpora. The results of the paper show that the most significant interjections and interjectional phrases in characters’ subcorpora are catchphrases that make their idiolect different from others. Thus, interjections not only express characters’ attitude or reaction to a situation but also reveal their personal traits.